Corticospinal tract insult alters GABAergic circuitry in the mammalian spinal cord - Russ, Jeffrey B.; Verina, Tatyana; Comer, John D.; Comi, Anne M.; Kaltschmidt, Julia A. (Frontiers in Neural Circuits, 2013)
During perinatal development, corticospinal tract (CST) projections into the spinal cord help refine spinal circuitry. Although the normal developmental processes that are controlled by the arrival of corticospinal input are becoming clear, little is known about how perinatal cortical damage impacts specific aspects of spinal circuit development, particularly the inhibitory microcircuitry that regulates spinal reflex circuits. In this study, we sought to determine how ischemic cortical damage impacts the synaptic attributes of a well-characterized population of inhibitory, GABAergic interneurons, called GABApre neurons, which modulates the efficiency of proprioceptive sensory terminals in the sensorimotor reflex circuit. We found that putative GABApre interneurons receive CST input and, using an established mouse model of perinatal stroke, that cortical ischemic injury results in a reduction of CST density within the intermediate region of the spinal cord, where these interneurons reside. Importantly, CST alterations were restricted to the side contralateral to the injury. Within the synaptic terminals of the GABApre interneurons, we observed a dramatic upregulation of the 65-isoform of the GABA synthetic enzyme glutamic acid decarboxylase (GAD65). In accordance with the CST density reduction, GAD65 was elevated on the side of the spinal cord contralateral to cortical injury. This effect was not seen for other GABApre synaptic markers or in animals that received sham surgery. Our data reveal a novel effect of perinatal stroke that involves severe deficits in the architecture of descending spinal pathways, which in turn appear to promote molecular alterations in a specific spinal GABAergic circuit.